When is it too Small to be Born? - Kimera, Charles Lukanga; Lukolo, Linda N. (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2020)
Low birth weight is the leading cause of perinatal and child mortality and contributes to several disabilities among survivors. It commonly results from preterm birth either with intact membranes or following preterm premature rupture of membranes. Proper knowledge of risk factors of low birth weight is important for identifying mothers at risk in order to properly plan and take appropriate actions before or immediately after delivery to prevent these poor outcomes. In this review paper, we looked at the subdivision of low birth weight, risk factors for preterm birth, consequences of low birth weight, threshold for viability as well as the interventions to reduce infant morbidity and mortality.